Comparative analysis of prodigiosin isolated from endophyte Serratia marcescens. (8th February 2018) - Khanam, B.; Chandra, R.
Abstract: Extraction of pigments from endophytes is an uphill task. Up till now, there are no efficient methods available to extract the maximum amount of prodigiosin from Serratia marcescens . This is one of the important endophytes of Beta vulgaris L. The present work was carried out for the comparative study of six different extraction methods such as homogenization, ultrasonication, freezing and thawing, heat treatment, organic solvents and inorganic acids to evaluate the efficiency of prodigiosin yield. Our results demonstrated that highest extraction was observed in ultrasonication (98·1 ± 1·7%) while the lowest extraction by freezing and thawing (31·8 ± 3·8%) methods. However, thin layer chromatography, high‐performance liquid chromatography and Fourier transform infrared data suggest that bioactive pigment in the extract was prodigiosin. To the best of our knowledge, this is the first comprehensive study of extraction methods and identification and purification of prodigiosin from cell biomass of Ser. marcescens isolated from Beta vulgaris L. Significance and Impact of the Study: The prodigiosin family is a potent drug with anticancer, antimalarial, antibacterial, antifungal, antiproliferative and immunosuppressive activities. Moreover, it has immense potential in pharmaceutical, food and textile industries. For the industrial perspective, it is essential to achieve purified, high yield and cost‐effective extraction of prodigiosin. To the best of our knowledge, this is the first comprehensive study on prodigiosin extraction and also the first report on endophyte Serratia marcescens isolated from Beta vulgaris L. The significance of our results is to extract high amount and good quality prodigiosin for commercial application. Abstract : Significance and Impact of Study: The prodigiosin family is a potent drug with anticancer, antimalarial, antibacterial, antifungal, antiproliferative and immunosuppressive activities. Moreover, it has immense potential in pharmaceutical, food and textile industries. For the industrial perspective, it is essential to achieve purified, high yield and cost‐effective extraction of prodigiosin. To the best of our knowledge, this is the first comprehensive study on prodigiosin extraction and also the first report on endophyte Serratia marcescens isolated from Beta vulgaris L. The significance of our results is to extract high amount and good quality prodigiosin for commercial application.